Avaliação da composição química, biológica e sensorial das folhas da Talinum paniculatum (Jacq.) Gaertn - Marcon, Caroline Toigo (2022)
Talinum paniculatum (Jacq.) Gaertn is an unconventional food plant (UFP) that grows in natural environments, without clearing new areas for planting and inputs, consumed in some regions of Brazil, but it is little explored. Thus, this study aimed to evaluate the chemical and mineral composition of Talinum paniculatum from the leaves, obtain extracts and evaluate its antimicrobial and antioxidant activity, and its consumption potential both in nature and in preparations. The protein, ash, lipid, and moisture content were determined according to the Association of Official Analytical Chemists, and the carbohydrate content by difference, while the mineral profile was determined by ICP-OES. The aqueous and hydroalcoholic extracts were used to evaluate the antimicrobial activity by the colorimetric method by microdilution and the antioxidant activity by the ABTS, DPPH, FRAP, total phenolics, and flavonoids methods. With the leaves, three dishes were prepared (cream of mayonnaise, omelet, and salad) that were sensorially evaluated by 124 consumers. Talinum paniculatum presented a centesimal composition similar to the plants of the Talinaceae and Portulacaceae families. As for the mineral content, the high K, Mg, and Ca content stood out, followed by Na and Fe. As for antimicrobial activity, it was observed that for the concentrations tested, the hydroalcoholic extract was more efficient and that the Minimum Inhibitory Concentrations (MIC) for this extract remained between >55.6 and 0.86 mg/mL in the bacteria tested. The aqueous extract did not present bactericidal activity for the microorganisms tested. On the other hand, the aqueous extract presented a higher antioxidant potential for the DPPH, FRAP, and total phenolics method, being 7755.31 mg Trolox 100 g-1 , 1.576 mg Trolox 100 g1 , and 17135.33 mg gallic acid equivalents (GAE) 100 g-1 , while the hydroalcoholic extract was 4108.33 mg Trolox 100 g-1 , 0.977 mg Trolox 100 g-1 and 9646.69 mg GAE 100 g-1 , respectively. The hydroalcoholic extract showed better results by the ABTS method and for the determination of the flavonoid content, 2097.28 84 mg Trolox 100 g-1 and 2300.64 mg of quercetin (QE) 100 g-1 , compared to 1544.52 mg Trolox 100 g-1 and 157.42 mg QE 100 g-1 for the aqueous extract. The foods prepared had good sensory acceptability, especially the omelet, with an acceptability index above 80% for all evaluated attributes, in addition to being highly nutritious. This study presents innovative results regarding the biological properties of a littlestudied plant.